Monoamine oxidase B layer-by-layer film fabrication and characterization toward dopamine detection - Miyazaki, Celina Massumi; Pereira, Tamyris Paschoal; Mascagni, Daniela Branco Tavares [UNESP]; Moraes, Marli Leite de; Ferreira, Marystela (Elsevier B. V., 2016)
In this work nanostructured film composites of the monoamine oxidase B (MAO-B) enzyme, free or encapsulated in liposomes, were fabricated by the layer-by-layer (LbL) self-assembly technique, employing polyethylene imine (PEI) as polycation. Initially, the MAO-B enzyme was incorporated into liposomes in order to preserve its enzymatic structure ensuring their activity and catalytic stability. The LbL film growth was monitored by surface plasmon resonance (SPR) by gold resonance angle shift analysis after each bilayer deposition. Subsequently, the films were applied as amperometric biosensors for dopamine detection using Prussian Blue (PB) as the electron mediator. The biosensor fabricated by MAO-B incorporated into liposomes composed of DPPG:POPG in the ratio (1:4) (w/w) showed the best performance with a sensitivity of 0.86 (μA cm− 2)/(mmol L− 1) and a detection limit of 0.33 mmol L− 1.
Keywords: Amperometry; Dopamine detection; Layer-by-layer; Liposomes; Monoamine oxidase-b